Isolation and characterization of recombinant lambda gt11 bacteriophages expressing four different Mycobacterium intracellulare antigens. - Morris, S L (1990)
Four bacteriophages expressing different immunoreactive recombinant Mycobacterium intracellulare antigens were isolated from a lambda gt11 library with monoclonal antibodies to M. intracellulare. These four antibodies reacted with native M. intracellulare proteins of 54, 43, 40/38, and 22 kilodaltons. Southern blot hybridizations with DNA probes prepared from insert fragments of these bacteriophages confirmed the M. intracellulare derivation of the inserts. The physical maps of the immunoreactive phages were deduced by restriction enzyme digestions. The molecular weights of the expressed recombinant antigens were determined by Western (immuno-) blotting.